Causes of Poor Performance in Mathematics at School Education Examination (SEE) - Gnawali, Yagya Prasad (Ganeshman Darpan, 2024)
This study aims to explore the causes of poor performance in mathematics at secondary level in Nepal specially in community school. I used phenomenological qualitative research paradigm for this study. I took five sample participants who had taken poor result in mathematics in SEE. Similarly, I have taken corresponding interview of their mathematics teachers in their respective schools as well as their parents. I used unstructured interview guidelines to take their in-depth interview. Weak foundation in basic level, ineffective teaching methods, lack of confidence, lack of motivation, and insufficient practices are main causes of poor performance in mathematics at secondary level. This study reveals that a comprehensive strategy involving parents, teachers, and students themselves is needed to address low performance in SEE. Early detection and intervention can help enhance academic performance as well as the general success of students.